Measuring transit-oriented development (TOD) network complementarity based on TOD node typology - Huang, Runjie; Grigolon, Anna; Madureira, Mafalda; Brussel, Mark (Journal of Transport and Land Use, 2018)
Recent research on the assessment of transit-oriented development (TOD) has focused on individual transit nodes. However, we argue that having such a TOD level value is not sufficient to understand the role each transit node plays within a TOD network. In other words, a transit node may have a low performance when evaluating its individual TOD level, but it may serve an important role within the TOD network, for example, as a feeder node. In this paper, a TOD typology was developed based on built-form indicators to identify the roles different types of nodes play within the transit network and to discuss complementarity effects between TOD nodes within the TOD network. The study area is the Arnhem-Nijmegen city region in the Netherlands, which has a TOD network of 22 train stations. Results identified three types of roles: suburban residential, characterized by low population and job densities; urban residential, marked by low destination accessibility and low diversity of land-uses; and urban mixed core, which featured higher densities of jobs, population, and diversity of land uses. Based on the TOD typology, a correspondence analysis was conducted to measure the potential complementarity effect of the TOD network system, i.e., the extent to which nodes in different typologies can complement each other to strengthen the characteristics of the TOD as a network. The results illustrated that differentiation among the TOD nodes in terms of residential housing prices and building uses contributed to a more diversified offer in terms of activities and functions of the TOD region and indicates complementarity between stations. Thus, TOD should be assessed and planned in a network system perspective, with the understanding that the nodes are pieces that contribute to the performance of the network.